Public finance in theory and practice - Musgrave, Richard A.; Musgrave, Peggy B. (New York : McGraw-Hill Book Co., 1989)
The book deals with many of the central economic and social issues of our time like issues that call for resolution by public policy because they cannot be handled adequately through a decentralized market
Includes bibliographical references and index.
opc 28/09/16
Loans
Keywords: Finance, Public